Child Care within the Framework of Social Policy: A Study of the Implementation of the Minister of Social Affairs Regulation No. 30 of 2011 at LKSA Karya Utama, Jayapura Regency - Rahmad Andre Ramadhan; Septyan Berliana Sumaki; Eka Nurwahyuliningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The implementation of the Minister of Social Affairs Regulation Number 30 of 2011 concerning the National Standards of Child Care in Child Welfare Institutions at Karya Utama Child Welfare Institution (LKSA) in Jayapura Regency is grounded in the importance of strengthening child care services based on children's rights and social welfare principles, as well as addressing the various limitations still encountered in the implementation of child care standards within child welfare institutions. This study employed a qualitative approach using a descriptive research method. Data were collected through observation, interviews, and documentation. The analysis was guided by George C. Edward III’s policy implementation theory, which encompasses the dimensions of communication, resources, disposition, and bureaucratic structure. The findings indicate that LKSA Karya Utama has implemented several forms of child care services, including the fulfillment of basic needs, educational support, religious guidance, and social assistance. However, the implementation of the National Standards of Child Care has not yet been fully optimized, particularly in the areas of family-based care, comprehensive child assessment, care documentation, and the availability of professional human resources. This study concludes that the implementation of child care policies is influenced not only by the existence of regulatory frameworks but also by institutional readiness, human resource capacity, and the support of social service networks in ensuring sustainable child welfare services.